Influence of Sewerage Network on Groundwater, Using Radiogenic Isotope Tritium - Singh, Jiban; Davis, Deljo; Somashekar, R. K.; Shivanna, K. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Radiogenic isotope tritium (3H) together with chemical compositions of water was used to discriminate ground water age and recharge areas and probable recharge processes respectively in four valleys of Bangalore. Forty seven (47) grounds and twenty (20) surface water samples were collected to assess the TDS, EC, Salinity and 3H. The groundwater available in four valleys contained high 3H (>1TU), suggesting recent recharge and belong to 100% modern age. Modern recharge in the aquifer is influenced by the sewerage network and as a consequence groundwater contains higher TDS, EC, salinity and 3H.